65.0k views
1 vote
Complete the squarex^2+12x+4=0

User Eladio
by
4.4k points

1 Answer

3 votes

The given equation is

x^2 + 12x + 4 = 0

Subtracting 4 from both sides, we have

x^2 + 12x + 4 - 4 = 0 - 4

x^2 + 12x = - 4

To complete the square, the first step is to add the square of half of the coefficient of x to both sides of the equation. From the equation,

coefficient of x = 12

half of the coefficient of x = 12/2 = 6

square of half of the coefficient of x = 6^2

By adding 6^2 to both sides of the equation, we have

x^2 + 12x + 6^2 = - 4 + 6^2

(x + 6)^2 = - 4 + 36

(x + 6)^2 = 32

User Ismael Di Vita
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.